2006
DOI: 10.1063/1.2336744
|View full text |Cite|
|
Sign up to set email alerts
|

Proton radiation hardness of single-nanowire transistors using robust organic gate nanodielectrics

Abstract: In this contribution, the radiation tolerance of single ZnO nanowire field-effect transistors (NW-FETs) fabricated with a self-assembled superlattice (SAS) gate insulator is investigated and compared with that of ZnO NW-FETs fabricated with a 60nm SiO2 gate insulator. A total-radiation dose study was performed using 10MeV protons at doses of 5.71 and 285krad(Si). The threshold voltage (Vth) of the SAS-based ZnO NW-FETs is not shifted significantly following irradiation at these doses. In contrast, Vth paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…On the other hand, transistors where the gate dielectric was a self-assembled superlattice ͑SAS͒ organic material instead of SiO 2 were much less sensitive to the irradiation. The difference was attributed to the generation of significantly less bulk oxide traps and interface traps in the SAS under proton irradiation 540 Er doping of ZnO NWs using 50 keV MEVVA ion implantation of Er to a dose of 5 ϫ 10 15 ions/ cm 2 was examined with optical applications in mind. 541 After oxygen annealing at 800°C, the implanted NWs were reported to retain a high crystalline quality and show room temperature luminescence at 1.54 m, suggesting the NWs could be used as functional units for optical communication applications.…”
Section: -46mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, transistors where the gate dielectric was a self-assembled superlattice ͑SAS͒ organic material instead of SiO 2 were much less sensitive to the irradiation. The difference was attributed to the generation of significantly less bulk oxide traps and interface traps in the SAS under proton irradiation 540 Er doping of ZnO NWs using 50 keV MEVVA ion implantation of Er to a dose of 5 ϫ 10 15 ions/ cm 2 was examined with optical applications in mind. 541 After oxygen annealing at 800°C, the implanted NWs were reported to retain a high crystalline quality and show room temperature luminescence at 1.54 m, suggesting the NWs could be used as functional units for optical communication applications.…”
Section: -46mentioning
confidence: 99%
“…539 The radiation tolerance of ZnO FETs was studied from a different point of view in a multilayer transistor setup where the NW was embedded below a SiO 2 passivation layer. 540 The NWs were irradiated with 10 MeV protons to fluences of 10 10 and 5 ϫ 10 11 protons/ cm 2 ͓doses of 5.71 and 285 krad͑Si͔͒, corresponding to doses expected over 2 weeks and 2 years in low-earth orbit in space. SiO 2 -based transistor structures were found to be highly sensitive to the irradiations, with already the lower dose leading to strong changes in electrical characteristics.…”
Section: -46mentioning
confidence: 99%
“…1(b) presents a schematic illustrating the generation of electron-hole pairs and the charge build-up in an SiO 2 dielectric layer by proton irradiation [14]- [16]. The silicon dioxide in our ZnO nanowire FET structure is sensitive to ionizing radiation [16], [17]. It has been shown that ZnO is much more resistant to high-energy proton bombardment than other semiconductors, such as Si, GaAs, and GaN [17]- [19].…”
Section: B Device Scheme and Characterization Methodologymentioning
confidence: 99%
“…The silicon dioxide in our ZnO nanowire FET structure is sensitive to ionizing radiation [16], [17]. It has been shown that ZnO is much more resistant to high-energy proton bombardment than other semiconductors, such as Si, GaAs, and GaN [17]- [19]. PI is also durable against exposure to the proton beam [20].…”
Section: B Device Scheme and Characterization Methodologymentioning
confidence: 99%
“…The irradiation of a ‐IGZO with electrons or multicomponent secondary particles is known to produce device characteristic changes although the underlying physicochemical mechanisms have not been investigated in detail . Interestingly, the flexible chemical bonding in amorphous materials also resulted in the realization of rad‐hard materials with the dynamic regeneration of any internal defects . Compared to permanent structural damage such as atomic displacement and vacancy generation in sc ‐Si after high‐energy (17 MeV) proton irradiation, the flexible metastable structure of a ‐Si could reconfigure the damaged bonding .…”
Section: Introductionmentioning
confidence: 99%